The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1158/1078-0432.ccr-15-0133
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoethnicity in Paclitaxel-Induced Sensory Peripheral Neuropathy

Abstract: Purpose Paclitaxel is used worldwide in the treatment of breast, lung, ovarian and other cancers. Sensory peripheral neuropathy is an associated adverse effect that cannot be predicted, prevented or mitigated. To better understand the contribution of germline genetic variation to paclitaxel-induced peripheral neuropathy, we undertook an integrative approach that combines genome-wide association study (GWAS) data generated from HapMap lymphoblastoid cell lines (LCLs) and Asian patients. Methods GWAS was perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 56 publications
(75 reference statements)
3
52
0
Order By: Relevance
“…Previously, human iPSC-derived neurons have been evaluated to screen for neurotoxic compounds [Ryan, et al 2016]. Our laboratory has used commercially available iPSC-derived cortical neurons to evaluate their potential as a model of neurotoxicity [Wheeler, et al 2015] and to functionally validate genes identified in human clinical genome wide association studies of peripheral neuropathy following treatment with paclitaxel [Wheeler, et al 2015, Komatsu, et al 2015], vincristine [Diouf, et al 2015] and docetaxel [Hertz, et al 2016]. Our work reported here extends previous studies to evaluate mechanistically distinct chemotherapeutics in iPSC-derived cortical and peripheral neurons, for effects on morphological characteristics and electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, human iPSC-derived neurons have been evaluated to screen for neurotoxic compounds [Ryan, et al 2016]. Our laboratory has used commercially available iPSC-derived cortical neurons to evaluate their potential as a model of neurotoxicity [Wheeler, et al 2015] and to functionally validate genes identified in human clinical genome wide association studies of peripheral neuropathy following treatment with paclitaxel [Wheeler, et al 2015, Komatsu, et al 2015], vincristine [Diouf, et al 2015] and docetaxel [Hertz, et al 2016]. Our work reported here extends previous studies to evaluate mechanistically distinct chemotherapeutics in iPSC-derived cortical and peripheral neurons, for effects on morphological characteristics and electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, knockdown of VAC14 seemed to decrease cellular sensitivity to paclitaxel treatment for these morphological characteristics suggesting that this gene may play an important role in the damage to processes and branching induced by docetaxel but not paclitaxel. A similar model of human neuronal cell sensitivity that utilizes induced pluripotent cortical neurons (iCell ® Neurons) has previously been used for mechanistic validation of GWAS hits that increases risk of paclitaxel-induced neuropathy(19, 33) and vincristine-induced neuropathy(11). These human model systems have several advantages over the use of rodent cell lines such as rat pheochromocytoma cell lines, PC12 or NS1.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar integration method using Asian cell lines and patient cohorts, when focusing more on Asian specific genes, decreased AIPL1 was found to result in decreased sensitivity of neurons to paclitaxel. In addition, breakpoint cluster region protein (BCR) was also identified to protect the neurons from paclitaxel induced toxicity [38]. Furthermore, using the CALGB 40101 patient cohort, paclitaxel-induced peripheral neuropathy was found to be heritable.…”
Section: Pharmacogenomics Of Cipnmentioning
confidence: 99%